Analysis of Acoustical Characteristics and Some Recommendations for Different Educational Rooms - GÓMEZ ESCOBAR, Valentın; BARRIGÓN MORILLAS, Juan Miguel (Archives of Acoustics, 2013)
Acoustic parameters were analysed in nine auditoria and multi-purpose confer-ence rooms in the University of Extremadura. Parameters related to the reverber-ation time, background noise, and intelligibility (both physical measurements ofdifferent parameters [Definition (D-50) and STI] and speech tests used to study thesubjective response of listeners) were studied. The measurements were comparedwith some recommendations from the literature and, considering that speech wasthe main use of the studied rooms, with the intelligibility results. Some differentrecommendations for reverberation times taken from the literature were analysed.The intelligibility results obtained from the measurements were also compared withthe intelligibility results that were determined by the speech tests.